1986
DOI: 10.1172/jci112606
|View full text |Cite
|
Sign up to set email alerts
|

Aggregating human platelets cause direct contraction and endothelium-dependent relaxation of isolated canine coronary arteries. Role of serotonin, thromboxane A2, and adenine nucleotides.

Abstract: Aggregating human platelets contract isolated rings of canine coronary artery without endothelium, but relax rings with intact endothelium. We performed experiments to identify the substances released from platelets responsible for these effects. The contraction in rings without endothelium was reduced by treating the platelets with the thromboxane synthetase inhibitor, dazoxiben, or treating the vessels with the thromboxane-receptor antagonist, SQ 29548. The serotonergic antagonist, methiothepin, also reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
68
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(70 citation statements)
references
References 26 publications
(35 reference statements)
1
68
1
Order By: Relevance
“…34 - 35 In contrast, in arteries with denuded endothelium, platelets produce contraction that appears to be mediated by thromboxane and serotonin. 35 Several studies indicate that aggregation of platelets can reduce blood flow, 8 11 demonstrated a cyclic reduction in coronary blood flow in dogs caused by periodic formation of platelet aggregates at the site of endothehal injury followed by spontaneous dissolution.…”
Section: Mechanisms Of Altered Vascular Response To Activated Plateletsmentioning
confidence: 99%
“…34 - 35 In contrast, in arteries with denuded endothelium, platelets produce contraction that appears to be mediated by thromboxane and serotonin. 35 Several studies indicate that aggregation of platelets can reduce blood flow, 8 11 demonstrated a cyclic reduction in coronary blood flow in dogs caused by periodic formation of platelet aggregates at the site of endothehal injury followed by spontaneous dissolution.…”
Section: Mechanisms Of Altered Vascular Response To Activated Plateletsmentioning
confidence: 99%
“…Inhibition of thromboxane A 2 production using a thromboxane synthase blocker (dazoxiben) or a thromboxane A 2 receptor antagonist (SQ29,548) attenuated contraction of the denuded coronary artery rings in response to aggregating platelets. 12 These results indicate that thromboxane A 2 is an important mediator of plateletinduced coronary artery constriction, whereas an intact endothelium is necessary for the relaxation of coronary artery segments in response to platelet aggregation. The purpose of this study was to determine the effects of intravascular platelet activation on coronary collateral blood flow by measuring the response to PAF in an in vivo canine model.…”
mentioning
confidence: 78%
“…Infusion of PAF into the normal coronary circulation typically yields a biphasic response, with initial vasodilation followed by vasoconstriction. 9 -11 Houston et al 12 observed that exposure of isolated coronary artery rings to aggregating platelets resulted in relaxation, but after removal of the endothelium, exposure to aggregating platelets caused contraction. Inhibition of thromboxane A 2 production using a thromboxane synthase blocker (dazoxiben) or a thromboxane A 2 receptor antagonist (SQ29,548) attenuated contraction of the denuded coronary artery rings in response to aggregating platelets.…”
mentioning
confidence: 99%
See 2 more Smart Citations